A mediastinal tumour that disappeared and reappeared - Senanayake, M. P.; Ajanthan, R.; S P Sumanasena, S. P.; Lamabadusuriya, S. P. (Sri Lanka college of pediatricians, 2003)
An 11 year old boy developed breathlessness over 12 days and was admitted to the local hospital with facial oedema and engorged neck veins. He had been "less active" and "feeling unwell" for one month. His father had been diagnosed and treated for pulmonary tuberculosis in the past year. Chest x ray showed a superior mediastinal mass (Figure 1). To relieve increasing respiratory difficulty he had been administered intravenous hydrocortisone 100 mg six hourly for 2 days followed by oral dexamethasone 4 mg six hourly for 6 days eight days prior to transfer to Colombo.

An 11 year old boy developed breathlessness over 12 days and was admitted to the local hospital with facial oedema and engorged neck veins. He had been "less active" and "feeling unwell" for one month. His father had been diagnosed and treated for pulmonary tuberculosis in the past year. Chest x ray showed a superior mediastinal mass (Figure 1). To relieve increasing respiratory difficulty he had been administered intravenous hydrocortisone 100 mg six hourly for 2 days followed by oral dexamethasone 4 mg six hourly for 6 days eight days prior to transfer to Colombo.
Keywords: mediastinal tumour